2022
DOI: 10.1109/tnnls.2021.3059912
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Reinforcement Learning With Universal Policies for Multistep Robotic Manipulation

Abstract: Multi-step tasks, such as block stacking or parts (dis)assembly, are complex for autonomous robotic manipulation. A robotic system for such tasks would need to hierarchically combine motion control at a lower level and symbolic planning at a higher level. Recently, reinforcement learning (RL) based methods have been shown to handle robotic motion control with better flexibility and generalisability. However, these methods have limited capability to handle such complex tasks involving planning and control with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 12 publications
0
19
0
Order By: Relevance
“…It is then potentially fruitful to develop a better curriculum for such tasks. Another interesting direction is to leverage task decomposition for multi-step tasks and make use of hierarchical learning systems [18]. The use of sub-goals is a promising way to tackle the hard exploration problem in such tasks.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is then potentially fruitful to develop a better curriculum for such tasks. Another interesting direction is to leverage task decomposition for multi-step tasks and make use of hierarchical learning systems [18]. The use of sub-goals is a promising way to tackle the hard exploration problem in such tasks.…”
Section: Challenges and Opportunitiesmentioning
confidence: 99%
“…To improve readability, the original set of tasks is named 'single-step tasks' and the new set of tasks is named 'multi-step tasks'. The multi-step tasks are developed with the aim to inspire new learning algorithms that can handle tasks where the reward signals only appear near the end of the task horizon [5,18]. Beside the delayed rewards, these tasks also require multiple steps to complete, and some of the steps are strongly dependent.…”
Section: Introductionmentioning
confidence: 99%
“…O VER the past few years, RL has achieved impressive success in a wide variety of tasks, including games [1]- [5] and robotic control [6]- [11]. Specifically, on continuous control, actor-critic RL algorithms [12]- [15] have been widely explored with remarkable performance.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by this, we propose firstly to leverage abstract demonstrations, which provide the correct order of steps to a learning agent instead of low-level motions. It has been shown that, given an efficient enough algorithm to learn the subtasks such as hindsight experience replay, abstract demonstrations can accelerate learning for multi-step tasks [5]. The main benefits of abstract demonstrations when compared to demonstrations of motion trajectories [6], [7] are: 1) they do not encode a specific pattern of the behaviours when solving a task; 2) they release robotic operators from the tedious processes of collecting motion trajectory data.…”
Section: Introductionmentioning
confidence: 99%